Cysticercosis of conus medullaris: A case report and literature review - Saurabh K. Verma; Vijay Kumar Gupta; M. Narayan Swamy; Harish C. Pathak (Indian Journal of Neurosurgery)
“Neurocysticercosis” - involvement of the central nervous system (CNS) by taenia solium, is one of the most common parasitic diseases of the CNS. However, spinal involvement by neurocysticercosis is uncommon. Spinal intramedullary cysticercosis involving the conus medullaris is an uncommon clinical condition, which may mimic an intramedullary tumor and can lead to irreversible neurological deficits if untreated. Here, we report a 31-year-old male patient with cysticercosis in the conus medullaris of the spinal cord. Magnetic resonance imaging revealed a well-defined round intramedullary lesion at D12-L1 vertebral levels, which was homogeneously hypointense on T1WI and hyperintense on T2WI with peripheral edema. Since the patient had progressive neurological deficits, surgery was performed to decompress the spinal cord. Histopathology examination of the removed lesion proved it to be cysticercosis. In this report, we also discuss the principles of diagnosis and treatment of intramedullary cysticercosis in combination with literature review.